Match Injuries in English Youth Academy and Schools Rugby Union: An Epidemiological Study. (April 2013) - Palmer-Green, Deborah S.; Stokes, Keith A.; Fuller, Colin W.; England, Michael; Kemp, Simon P.T.; Trewartha, Grant
Background: Numerous injury epidemiology studies have reported injury patterns in senior rugby union, but investigations in youth rugby are limited. Purpose: To describe the nature of injuries resulting from match play within the English youth rugby union, including a comparison between 2 levels of play within the same age group: professional academy versus school rugby. Study Design: Cohort study; Level of evidence, 2. Methods: A 2-season (2006-2007 and 2007-2008) study obtained information on injuries sustained in male youth rugby union players (age, 16-18 years) from 12 English Premiership academies (n = 250) and 7 schools (n = 222). Match exposure (player-hours) and injury details were recorded. Results: Match injury incidence was 47 per 1000 player-hours for the academy and 35 per 1000 player-hours for the school groups; these rates were statistically different ( P = .026). The most common injury site was the lower limb and the most common injury type was a ligament sprain, with injuries to the knee and shoulder region resulting in the greatest burden of injury for both groups. The tackle event was the most common cause of match injury for both academy (51% of injuries) and school (57% of injuries) groups. Conclusion: Overall, the incidence of injury for youth rugby was lower than for previous studies in senior rugby, but injury patterns (location, type) and causes were similar. The study confirmed that match injury incidence was significantly greater in elite academy youth rugby union than schools rugby. The results suggest that the specific focus for injury risk management in youth rugby should be on players' tackle technique and prevention strategies for knee and shoulder injuries.